A novel mechanism for grazing lawn formation: large herbivore‐induced modification of the plant–soil water balance. (9th September 2014) - Veldhuis, Michiel P.; Howison, Ruth A.; Fokkema, Rienk W.; Tielens, Elske; Olff, Han; Schwinning, Susan
Summary Large herbivores play a key role in creating spatial heterogeneity through the formation of grazing lawns. Recent research suggests that the currently accepted nutrient‐based theory on the formation of these grazing lawns cannot universally explain their formation in all ecosystems where they are found. We developed and investigated an alternative hypothesis on grazing lawn formation and maintenance based on herbivore effects on the plant–soil water balance. We propose that large herbivores change the soil water balance in grazing lawns through defoliation and soil compaction, causing a shift in vegetation composition towards a drought‐tolerant plant community. Investigating this idea in a tropical savanna, we indeed found profound differences in grazing lawn soil properties and water balance. In particular, defoliation increased soil temperatures and potential evaporation rates while soil compaction increased bulk density and decreased water infiltration rates, especially on fine‐textured soils. Soil moisture was therefore generally much lower in grazing lawns than in adjacent bunch grass areas. Furthermore, we found that grazing lawn species show drought‐tolerant traits, with higher leaf sodium levels, suggesting evolutionary adaptation to these herbivore‐induced dry conditions. However, leaf water potentials did not differ between grazing lawn and bunch grass species. Synthesis. This study shows that large herbivores might form grazing lawns through previously underestimated effects on water balance. Thus, future studies on large herbivore effects on vegetation should increasingly focus on additional pathways of soil compaction and defoliation. While nutrient‐based processes driving grazing lawn formation may operate during the wet season in savannas, we suggest that water balance‐based processes are additionally important during the dry season.